A Conflict Management Model to Develop Teacher Performance at Muhammadiyah Wirobrajan III Elementary School, Yogyakarta - Wahyuni, Sri; Santosa, Achadi Budi; Maryani, Ika (Universitas Ahmad Dahlan, 2025)
This study aims to analyze an effective conflict management model in improving teacher performance at Muhammadiyah Wirobrajan III elementary school Yogyakarta. Conflict in the workplace, especially in educational environments, often affects the productivity and performance of educators. Therefore, good conflict management is very important to create a conducive working atmosphere and improve the quality of teaching. This study uses a qualitative research method by collecting data obtained through in-depth interviews, observations, and document analysis to examine conflict management at Muhammadiyah Wirobrajan III elementary school. This study focuses on how internal conflicts in schools are handled and how these management strategies affect teacher performance. Data collection was carried out through interviews with the principal, teachers, and staff, as well as direct observation of the school environment. The results of the study indicate that unresolved conflicts can hinder teacher productivity, which ultimately impacts the quality of education. Therefore, the application of an effective conflict management model is very important. This study identifies key strategies in conflict resolution, including early detection of conflict, thorough analysis, and selection of appropriate solutions to resolve disputes constructively. The proposed conflict management model emphasizes a collaborative approach, encouraging conflicting parties to work together to find mutually beneficial solutions. This model aims to improve teacher performance, improve teaching quality, and support the achievement of educational goals. This study contributes to the field of educational management, especially in conflict resolution strategies to improve teacher performance.